Black victory : the rise and fall of the white primary in Texas - Hine, Darlene Clark (University of Missouri Press, 2003)
"In Black Victory, Darlene Clark Hine examines a pivotal breakthrough in the struggle for black liberation through the voting process. She details the steps and players in the 1944 U.S. Supreme Court decision in Smith v. Allwright, a precursor to the 1965 Voting Rights Act. She discusses the role that NAACP attorneys such as Thurgood Marshall played in helping black Texans regain the right denied them by white Texans in the Democratic Party: the right to vote and to have that vote count. Hine illuminates the mobilization of black Texans. She effectively demonstrates how each part of the African American community - from professionals to laborers - was essential to this struggle and the victory against disfranchisement."--Jacket.